Singapore ‘Herstory' : from Sophia Raffles to Kwa Geok Choo and beyond - Chew, Emrys (2011)
Tributes continued to pour in for the late Kwa Geok Choo, wife of Singapore’s Minister Mentor Lee Kuan Yew and mother of Singapore’s Prime Minister Lee Hsien Loong. Following her demise on 2 October 2010, the